Hydrological control, fractionation, and fluxes of dissolved rare earth elements in the lower Orinoco River, Venezuela. (January 2020) - Mora, Abrahan; Moreau, Cristina; Moquet, Jean-Sébastien; Gallay, Marjorie; Mahlknecht, Jürgen; Laraque, Alain
Abstract: The monthly variation of dissolved rare earth elements (REEs) was assessed in the lower Orinoco River during a two year period (2007–2008) to determine the seasonal variability of REE concentrations, to identify the variables that exert the main control in their concentrations and fractionation, and to quantify the annual fluxes of dissolved REEs to the Orinoco estuary. Overall, the abundance of dissolved REEs is dominated by hydrological variations in the water discharge, wherein the lowest concentrations and greater fractionation occur during low water-discharge periods. The pH and Al- and Fe-mineral colloids are identified as the main variables that control both the abundance and fractionation of dissolved REEs. An enrichment of heavy REEs (HREEs) relative to light REEs (LREEs) occurs at circumneutral and alkaline pH values. However, the logarithmic relationships between the YbUCC /NdUCC ratios and Al and Fe concentrations indicate that Al- and Fe-mineral colloids are responsible for the progressive enrichment of LREEs relative to HREEs under acidic conditions. The Ce and Eu anomalies are also dominated by variations in the water discharge. Negative Ce-anomalies are observed during low flow periods. This is probably due to the signature of the Andean host rocks and/or the oxidation and co-precipitation of Ce (III) to CeO2 at alkaline pH. However, the lesser Ce fractionated values during flood/high-water periods may indicate less oxidized/more reduced source conditions during these periods. Conversely, positive Eu anomalies are observed during low-water periods because of the preferential weathering of plagioclase in shield terranes and Eu-bearing minerals in the Andes. The fluxes of dissolved REEs from the lower Orinoco River to the Orinoco estuary display strong inter-annual variations, which range from 45.6% for Lu to 56.5% for Gd. These results highlight the importance of performing monthly and inter-annual REE time series in order to develop a more precise quantification of the annual REE fluxes from large rivers to the oceans. Highlights: The Orinoco River displays a broad range of REE concentrations along the hydrological year. Alkaline pH water results in lower REE concentrations and more REE fractionation. Acidic water and Al- and Fe-colloids increase the dissolved LREE abundance. Aqueous Eu and Ce anomalies are controlled by variations in water discharge. The mean annual flux of dissolved Nd of the Orinoco River was 336 t.